Kemampuan Translasi Representasi Verbal ke Simbolik ditinjau dari Adversity Quotient (AQ) Tipe Climber dan Camper - Ramadhan, Fista Cahyani; Patmawati, Hetty; Mulyani, Eva (Universitas PGRI Semarang, 2025)
This study aims to analyze the ability to translate verbal representations into symbolic representations in terms of adversity quotient (AQ) types climber and camper. This study uses a qualitative approach with a descriptive method. Data collection techniques in this study were carried out through the distribution of ARP questionnaires, tests of the ability to translate verbal representations into symbolic representations, and interviews. The instruments used were the ARP questionnaire and a test of the ability to translate verbal representations into symbolic representations of single-variable linear inequalities. The subjects of this study included two eighth-grade students from SMP Negeri 15 Tasikmalaya. Data analysis was conducted using several techniques, including data reduction, data presentation, and conclusion drawing. The results of the study indicate that students with climber-type AQ are able to meet all indicators of verbal-to-symbolic representation translation ability, namely: identifying the information contained in the source representation; identifying what is being asked from the source representation; determining the strategy or initial steps for forming the source representation based on the target representation; forming the requested target representation as the solution to the target representation; and checking the consistency of the target representation with the source representation. Meanwhile, students with AQ type camper were able to meet four out of five indicators, with the unmet indicator being checking the consistency of the target representation with the source representation.